Optimization of process parameters for production of antimicrobial metabolites by an endophytic fungus Aspergillus sp. CPR5 isolated from Calotropis procera root. - VERMA, SHIV KR.; Lal, Moti; (DAS), MIRA DEBNATH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:To study the antimicrobial activity of crud ethylacetate extract from endophytic fungus in Calotropis procera root. Methods:Endophytic fungus was screened for production of antimicrobial metablites.fermentation was carried out in 500 ml Erlenmeyer flask. Disc diffusion method was used to test antimicrobial activity of crude extract using chloramphenicol sulphate and Flucnazole as positive controle Ressults: A total of fourteen Endophytic fungi were isolated (CPR1- CPR14). Among these fourteen isolates, CPR5 was found to show maximum antimicrobial activity, in compare to other isolates, against gram positive, gram negative bacteria and fungi. The antimicrobial activity was tested against Escherichia coli. Pseudomonas aeroginosa, Bacillus subtilis, Staphylococcus aureus, Ralstonia solanacearum, Xanthomonas oryzae, Penicillium chrysogenum, Candida albicans, Phoma exigua, Sclerotium rolfsii and Sclerotinia scleratiourum. Minimum inhibitory concentration (MIC) of crude extract against test microorganisms was determined. Fungus was identified as aspergillus sp. Prduction parameters (Temprature, pH, Carbon source, Nitrgen surce, Sdium Chlride concentration) were optimized. Conclusion: Crud extract produced by the isolated endophytic fungus could be an important source of broad spectrum antimicrobial metabolites. Keywords: Endophytic fungi, Antimicrobial metabolites, Process optimization, Calotropis procera, Inhibition zone.